Luise Gottsched the Translator. - Brown, Hilary (Studies in German Literature Linguistics and Culture, 118., 2012)
Critics have paid increasing attention to the oeuvre of Luise Gottsched (1713-62), Germany's first prominent woman of letters, but have neglected her lifelong work of translation: an extraordinary range of works from drama and poetry to philosophy, history, archaeology, even theoretical physics. This first overview of Gottsched's translations places them in the context of eighteenth-century intellectual, literary, and cultural history, showing that they were part of an ambitious program undertaken with her famous husband to shape German culture during the Enlightenment.